Developing KAED’s expert database - Yaali, Syarel Azill; Ayob, Mohd Fairullazi (2018)
• The project is proposed to develop an online database system in the present KAED website to improve the visibility of academics with specific reference to their established expertise and skills in KAED. • The present database systems, i.e. HURIS and IREP presented inconsistent information that cause difficulty to online users to retrieve exactly the established expertise and skills of the academics in the simplest form. • The actual statement of expertise is only available via the IREP system. • At the moment, no KCDIO have done it yet.